Receipts and payments account for the period 7th June, 1937 to 30th November, 1937
1938-01-03 034-0100-002 INTERNATIONAL BRIGADE DEPENDANTS AND WOUNDED AID COMMITTEE Receipts and Payments Account FOR THE PERIOD 7th JUNE to 30th NOVEMBER, 1937 RECEIPTS £ s. d. To Balance at Bank, 7/6/1937 639 13 9 Balance in Hand, 7/6/1937 81 16 292/946/34/100(ii)